The Benefit of TikTok Usage and It’s Effectiveness in Teaching English: A Systematic Review - Putri, Amelia; Billaizah, Adzra; Alizah, Ana Rosita; Prastiwi, Andini Eka; Tarihoran, Naf'an (Formosa Journal of Sustainable Research, 2024)
This study investigates the impact of TikTok on English language learning, acknowledging its global recognition. Employing a Systematic Review method aligned with PRISMA guidelines, the research delves into databases like Google Scholar, Directory of Open Access Journals (DOAJ), and Education Resources Information Center (ERIC), focusing on TikTok's relevance in English teaching. The findings indicate that TikTok positively influences students' speaking, listening, and writing skills, providing an interactive and engaging learning platform. The study concludes by emphasizing TikTok's potential as a valuable resource in language education, highlighting the need for further research to optimize its educational effectiveness. The implications suggest that educators can effectively utilize TikTok to enhance student engagement and improve language learning outcomes